Rapidly sheared homogeneous stratified turbulence in a rotating frame - Kassinos, S. C.; Akylas, Evangelos; Langer, C. A. (My University, 2007)
Rapid distortion theory is applied to stratified homogeneous turbulence that is sheared in a rotating frame. Insight into the stabilizing and destabilizing effects of the combined stratification and frame rotation is gained by considering initial fields that are two-dimensional, with the axis of independence aligned with the flow direction. For these conditions, we derive solutions for the Fourier components of the flow variables, and for one-point statistics in physical space. The analytical results are in qualitative agreement with the exact numerical solution for initially isotropic homogeneous turbulence, and they could be a reference point for the development of turbulence models.
Keywords: Turbulent flows; Tensor methods; Numerical solutions; Reynolds stress modeling; Rotating flows